2020
DOI: 10.28948/ngumuh.783613
|View full text |Cite
|
Sign up to set email alerts
|

Gida Takvi̇yeleri̇ Kullanim Alişkanliklarinin Değerlendi̇ri̇lmesi̇

Abstract: Bu araştırmanın amacı, ülkenin her bölgesinden tüketici fikri alınıp gıda takviyeleri hakkında tüketim sıklığının ve miktarının belirlenmesidir. Araştırma sonucunda ulaşılan veriler Minitab programı ile ortalama, olasılık değeri (p değeri), yüzde değerleri ve ki-kare (χ²) önemlilik testi kullanılarak değerlendirme yapılmıştır. Yapılan anket sonuçlarında 800 kişiden %35.3'ünün gıda takviyesi kullandığı belirlenmiştir. Tüketicilerin takviye kullanım sıklığı %45.1 oranında günde 1-2 defa olarak belirlenmiştir (p>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 2 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…44.3% of consumers stated that they took supplements from vitamins. 66 Çimke and Yıldırım Gürkan, 67 in their study of using Google Trends search volumes, revealed that interest in vitamins increased since the beginning of the pandemic both in Turkey and in the world. Also, in Turkey, ‘Food Supplement Use and Measurement of Eating Habits’ survey conducted by Food Supplements and Nutrition Association 68 revealed that usage of food supplements increased in the COVID‐19 period.…”
Section: Discussionmentioning
confidence: 99%
“…44.3% of consumers stated that they took supplements from vitamins. 66 Çimke and Yıldırım Gürkan, 67 in their study of using Google Trends search volumes, revealed that interest in vitamins increased since the beginning of the pandemic both in Turkey and in the world. Also, in Turkey, ‘Food Supplement Use and Measurement of Eating Habits’ survey conducted by Food Supplements and Nutrition Association 68 revealed that usage of food supplements increased in the COVID‐19 period.…”
Section: Discussionmentioning
confidence: 99%